Smoking among secondary school students in Kota Tinggi, Johor, Malaysia - findings from a cross-sectional study - Lim, Hock Kuang; Teh, Huey Chien; Lim, Li Hui; Lau, Joo Keng; Cheong, Chee Kee; Mohd Ghazali, Sumarni; Chan, Ying Ying; Sabtu, Mohd Yusoff; Ismail, Hasimah; Mohd Zaki, Nor Azian; Thomas, Leni Tupang; Lim, Kuay Kuang; et al. (Asian Pacific Organization for Cancer Prevention, 2015)
Smoking is a learnt behavior during adolescence and understanding the factor/s associated with smoking will assist in identifying suitable measures in combating the rising prevalence of smoking among adolescents. This research aimed to identify the factor/s associated with smoking among form four students in Kota Tinggi, Johor. Multistage sampling was used to select a representative sample of students in 2008 and data were collected using a self-administered validated questionnaire. This study revealed that the overall smoking prevalence was 19.0% with a significantly higher proportion of male smokers (35.8%) as compared to females (3.15%). Adolescents who were male (aOR 6.6, 95%CI 2.61-16.4), those who had peer/s who smoked (aOR 4.03, 95% CI 1.31-12.4), and those who studied in rural areas and Felda Settlements ( aOR 4.59, 95 CI 1.11-18.0; aOR 9.42, 95%CI 3.91-29.1) were more likely to smoke in the past one week. On the other hand, adolescents with better knowledge on the hazards of smoking and negative attitudes towards smoking were less likely to smoke (aOR 0.51, 95%CI 0.37-0.72; aOR 0.67, 95%CI 0.46-0.99). Future promotional and interventional programmes on smoking should be considered and the above identified risk factors integrated to reduce smoking prevalence among students of school-going ages in Kota Tinggi, Johor.